From the monks' way to people's way transmission and reformation of the Soraphan - Thotham, Awirut
This research aims to understand the underlying processes involved in transmitting the soraphan within the frames of the monks' Buddhist practices, particularly in adherence to the dharma in its emphasis of the sati (mindfulness, consciousness); to look at changes in the transmission of the soraphan particularly in the use of musical and lyrical elements (e.g., melody, words, chanting style or form). The changes can be observed from the teachings of the monks to people learning from each other in the current practices; to see the development of the soraphan through the passage of time and what has been formed through the intervention of the laypeople. The development will involve: a) looking at the existing literature about the soraphan in Isan, Thailand and Laos along the Maekhong River, and determine what have been explored in terms of traditional and new ways of teaching the vocal chant; b)knowing its traditional state to changes and innovation in structure and styles of interpretation; c) analyzing its form as a chant to a song with new melodies, rhythm, timbre, dynamics, poetic texts and adaptations of popular forms like morlam.